Seroprevalence of Hepatitis B and C among Oncology Patients in Turkey (Journal of Health, Population and Nutrition, 2012)
Hepatitis B virus (HBV) is one of the public-health issues worldwide. Approximately two billion people are infected with HBV, and about 350 million people are chronic carriers globally. About 3% of the world population is infected with hepatitis C virus (HCV). Oncology patients receiving packed red blood cell suspensions and other blood products usually are in the high-risk group for infections due to these viruses. The aim of the study was to detect the seroprevalence of hepatitis B and hepatitis C among chemotherapy patients at the Oncology Department of the Tepecik Education and Research Hospital. HBsAg, anti-HBs, anti-HBcIgM, anti-HBc total and anti-HCV assays were studied by enzyme immunoassay method (Diasorin, Italy) in serum samples of patients (n=448) referred to the Department of Oncology of the Tepecik Education and Research Hospital during 1 June 2006–1 January 2007. Of the 448 patients, 19 (4.2%) were HBsAg-positive, and three (0.7%) had anti-HCV positivity. In this study, the seroprevalence of HBV was similar to previous data in Turkey. This could be due to widespread vaccination programmes. The seroprevalence of low anti-HCV may be because of controlled blood transfusion. Oncology patients should be monitored for their protective antibody levels against HBV, and they must be included in the vaccination programme. Their anti-HCV status should also be checked as well. DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9903 JHPN 2011; 29(6): 652-655